Respuesta :

1) Now,

a + 27° = 90° (right angle triangle)

a = 63°

2) Now,

b + b + b = 90° (right angle triangle)

or, 3b = 90°

b = 30°

3) Now,

c + c + 40° = 90° (right angle triangle)

or, 2c = 90° - 40°

or, c = 50°/2

c = 25°

4) Here,

e = 41° (vertically opposite angle)

f = 82° ( vertically opposite angle)

Now,

d + e + f = 180° (straight angle)

or, d + 41° + 82° = 180°

or, d = 180° - 123°

d = 57°

Then,

g = d = 57° (vertically opposite angle)

It is all correct answer...

I hope u understand...

Thank you my cutie...

Mark me as brainliest...